(untitled) (Herald of Journalism, 2023)
The power of any society is the quality of knowledge. Journalism education has a decisive force in the socio-economic, political and cultural development of the state. The aim and main idea of the scientific article is to show the importance of fiction in the acquisition by journalism students of such qualities as creative erudition, value orientation, creativity and social thinking. The scientific and practical significance of the study is that fiction is a great spiritual force that provides a wise conceptual understanding of the problems of society and individuals, but the question of the influence of this important basis on creativity remains an open, unexplored side. In addition, scientific thought about creativity says: “Throughout the entire historical period of the development of philosophy, ideas about creativity have changed significantly. ...Each subsequent stage of research into this category enriched and expanded our knowledge both about it itself and about the possibility of independent creative activity of a person…” (Yagolkovsky S.R., 2007). This point of view also asserts the value of the topic of this study. The object of study of the problem is the legacy of Tleubergen Jumamuratov (1915-1990), People’s Poet of Uzbekistan and Karakalpakstan, laureate of the Berdakh State Prize, who was awarded the Order of the Badge of Honor, Friendship of Peoples, medals and Certificates of Honor from many countries. He worked in the media system and, moreover, for many years was the main consultant at the Writers’ Union of Karakalpakstan and had extensive experience working with young authors. He wrote quite a lot of instructions, poetic lessons about the tasks and responsibilities of a creative person to society. The methodology of the work – studying these materials that helps to solve a number of issues related to the training of creative journalists in higher education, as a spiritual, ideological experience, as a sharpening knowledge in the creative process.